Animal slurry sanitization through pH adjustment: process optimization and impact on slurry characteristics - Rodrigues, Joana (2021)
Sanitization by pH adjustment of dairy and pig slurries was evaluated for potential use as organic fertilizer in horticulture. This requires absence of Salmonella in 25 g of slurry and less than 1000 Escherichi coli colony-forming unit per gram of fresh slurry (Regulation (EU) 2019/1009). Additives used in the alkalinization and acidification treatments, included hydroxide-salts and nitrogen-based reactants to increase slurry pH to a basic range (9.0–11.0) and concentrated H2SO4 to decrease slurry pH to an acidic range (5.5–3.5). While low-cost urea was unable to increase the slurry pH above 9.5, ammonia efficiently increased slurry pH to the targeted values (but enhanced the emissions risk), whereas the effect of Ca(OH)2 was hindered by its low solubility. Slurry sanitization by alkalinization was achieved at a pH of 9.5 for both slurries, using similar quantities of KOH or NaOH. KOH was selected for further tests since it provides a plant macronutrient. Acidification with concentrated H2SO4 was able to achieve sanitization by lowering the pH to 5.0. After a 60-d storage experiment with raw and treated slurries, the level of E. coli was below the sanitization limit for all samples. Storage had no significant impact on slurry characteristics, except for ammonium-nitrogen content. Acidification treatment minimized ammonia losses